Problematika Seputar Kodifikasi Al-Qur'an - Munawir Munawir (MAGHZA, 2018)
Historically, the bookkeeping of the Koran is not as complicated as the books of Hadith. But that does not mean that the codification process of the Qur'an is not interesting to learn. In this case, there are a number of questions that remain relevant to convey; Is the Qur'an still true today? What is the true structure of the Qur'an? Are there standard standards for Koran arrangements agreed upon by Muslims throughout the world? These questions about the codification of the Qur'an often arise, because in the course of the Qur'an, in its capacity as a book (a piece of paper) is bound where there are dictums in Arabic that Muslims consider to be revelations from God - the codification process is no longer normative, but very historical, because related to various types of discourses (social, political, etc.) that surround it. In this context, historical and analytic studies of the historical codification of the Qur'an need to be presented, and this paper was written to meet those needs. Through the study of history based on Muslim scholarship about the history of the Quranic codification from the time of the Prophet Saw. to standardization in the form of reading and writing, which was then supplemented with critical analysis based on Western scholarship, it found that standardization "writing" the Qur'an in rasm Uá¹¡mÄnÄ« cultural products, and therefore open and allow for tashih, criticism, or even revision with more valid data findings. This does not mean the desecration of the Qur'an, but as a logical consequence of the existence of rasm Uá¹¡mÄnÄ« as something which is a human form.